2021
DOI: 10.1002/lary.29895
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy Versus Elective Node Dissection in Stage cT1‐2N0 Oral Cavity Cancer

Abstract: Objective: To compare overall survival (OS) and disease-free survival (DFS) between sentinel lymph node biopsy (SNB) and elective neck dissection (END) in the surgical management of cT1-2N0 oral cavity squamous cell carcinoma (OCSCC).Methods: English full-text articles were searched in PubMed and Embase on May 9, 2021. Articles had to compare SNB with END in cT1-T2N0 OCSCC patients; report hazard ratios (HRs), Kaplan-Meier curves, or P-values with total number of events for survival outcomes; be from a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
(132 reference statements)
0
14
5
Order By: Relevance
“…However, they included only six prospective studies and did not discuss DSS. Saleem et al found no significant difference in DFS or OS between patients who underwent SNB and END (37). However, unlike our study, their DFS data were heterogeneous.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, they included only six prospective studies and did not discuss DSS. Saleem et al found no significant difference in DFS or OS between patients who underwent SNB and END (37). However, unlike our study, their DFS data were heterogeneous.…”
Section: Discussioncontrasting
confidence: 93%
“…Thus, although the studies varied somewhat in terms of design and quality, the variations did not affect the results, and the survival outcomes of SNB and END were similar. In contrast to Saleem et al, we found no significant difference in OS, DFS, or DSS between SNB and END in any study (Figure 2), possibly because our subgroups were defined by follow-up period (3, 5, and 10 years) (9,37,39,40). Earlier meta-analyses did not perform subgroup analyses by follow-up period.…”
Section: Discussioncontrasting
confidence: 92%
“…Recent years have seen a growing body of evidence to indicate that SNLB, with completion neck dissection where necessary, has similar patient survival outcomes as END for the management of the N0 neck in early stage OSCC 8–11,20 . Furthermore, cost and quality of life analyses appear to favour SNLB over END in these patients 12,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen a growing body of evidence to indicate that SNLB, with completion neck dissection where necessary, has similar patient survival outcomes as END for the management of the N0 neck in early stage OSCC. [8][9][10][11]20 Furthermore, cost and quality of life analyses appear to favour SNLB over END in these patients. 12,21,22 Given these observations, several authorities recommend SLNB as the standard of care in cT1-2 N0 OSCC, while some professional bodies recommend that all patients with this disease should have access to the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the noninferiority margin was also pointed out by Lai et al 6 in 2020. Several meta-analyses 7,8 for SLNB indicated a nonsignificant difference in prognosis. Even if the overall survival were not equivalent, the difference would be too small to be detected by 550 patients on the two RCTs.…”
mentioning
confidence: 99%